BIOKONVERSI KULIT PISANG RAJA (Musa paradisiaca) DENGAN Rhizopus oligosporus TERHADAP PERUBAHAN KANDUNGAN BAHAN KERING, BAHAN ORGANIK DAN PROTEIN KASAR - Mokoolang, Mirsad C; Wolayan, F R; Imbar, M L; Toar, W L (Universitas Sam Ratulangi, 2018)
BIOCONVERSION OF BANANA PEEL Var. Raja (Musa paradisiaca) WITH Rhizopus oligosporus TO CHANGE OFDRY MATTER CONTENT, ORGANIC MATTER AND CRUDE PROTEIN. This study aims to determine the change of dry matter content, organic matter and crude protein in banana peel var. raja (Musa paradisiaca) fermented with Rhizopus oligosporus. The study was conducted for three weeks, using Completely Randomized Design (RAL) consisting of 9 treatments and each treatment was repeated 3 times. The treatment consisted of P1 (inoculum dose 0.2% and 48 hours fermentation time), P2 (inoculum dose 0.4% and 48 hours fermentation time), P3 (inoculum dose 0.6% and 48 hours fermentation time), P4 (inoculum dose 0.2% fermentation 96 hours), P5 (inoculum dose 0.4% and 96 hours fermentation time), P6 (inoculum dose 0.6% and 96 hours fermentation time), P7 (inoculum dose 0.2% and fermentation time 144 hours), P8 (inoculum dose 0.4% and fermentation time 144 hours) and P9 (inoculum dose 0.6% and fermentation time 144 hours). The results of variance indicated that the treatment of dose inoculum and fermentation time had a significant effect (P <0.05) on dry matter content, organic matter and crude protein. Based on the result of this research, it can be concluded that banana peel var. raja bioconversion (Musa paradisiaca) with Rhizopus oligosporus can increase percentage change of dry matter and crude protein but there is decrease of organic matter content. The use of 0.4% inoculum dosage and 96 hours of fermentation time (P5) could increase the percentage change of dry matter content by 6.55%, decrease the percentage change of organic matter content by 3.97% and increase the percentage change of crude protein content by 60, 91%.Â Keywords: Bioconversion, Banana Peel var. Raja, Rhizopus oligosporus